Total energy intake accounts for postnatal anthropometric growth in moderately/late preterm infants. (3rd May 2017) - Yagasaki, Hideaki; Murakami, Yasushi; Ohyama, Tetsuo; Koizumi, Keiichi; Hoshiai, Minako; Nakane, Takaya; Sugita, Kanji
Abstract: Objective : Moderately preterm (MP) (32–33 weeks) and late preterm (LP) (34–36 weeks) infants have higher risks of mortality and growth and developmental problems. We, herein present a new concept of nutritional assessment, total energy intake (TEI), which is the sum total of kilocalories administered in all nutrient forms. Methods : Fifty-two preterm infants were classified as MP ( n  = 12), LP/appropriate for gestational age (LP/AGA) ( n  = 33), or LP/small for gestational age (LP/SGA) ( n  = 7). All groups received nutrient therapy by the same protocol. The sum of the daily energy intake at 14 and 28 days after birth was determined. Results : TEI was 2822.1 ± 162.1 kcal/kg/28 days in the MP group, 3187.2 ± 265.0 kcal/kg/28 days in the LP/AGA group and 3424.6 ± 210.4 kcal/kg/28 days in the LP/SGA group. In all groups, TEI for 28 days was significantly correlated with body weight gain ( r  = 0.465, p  = 0.006). TEI for 14 days after birth was inversely correlated with the body weight loss rate after birth ( r  = −0.491, p  = 0.0002). Conclusion : TEI was well correlated with anthropometric changes after birth. TEI may be used to effectively assess preterm infants' nutritional needs.